The Mediating Effect of Depressive Symptoms on the Relationship between Adverse Childhood Experiences and Problematic Internet Use in Children and Adolescents - Seo, Jiyeong; Lee, Cheol-soon; Lee, Young-Ji; Lee, Mi-Sun; Bhang, Soo-Young; Lee, Dongyun (Journal of Korean medical science, 2020)
The purpose of this study was to evaluate the mediating effect of depressive symptoms on the relationship between adverse childhood experiences (ACEs) and problematic internet use. The study participants were 180 students between the ages of 9 and 18 years. Path analysis was performed to measure the relationships among ACEs, depressive symptoms and problematic internet use. ACEs significantly affected depressive symptoms (standardized regression weight, 0.36; P < 0.01), and depressive symptoms also affected problematic internet use (standardized regression weight, 0.40; P < 0.01). We found that depressive symptoms had a significant mediating effect on the relationship between problematic internet use and ACEs. The management of depressive symptoms would be important to prevent problematic internet use in children and adolescents with ACEs.The purpose of this study was to evaluate the mediating effect of depressive symptoms on the relationship between adverse childhood experiences (ACEs) and problematic internet use. The study participants were 180 students between the ages of 9 and 18 years. Path analysis was performed to measure the relationships among ACEs, depressive symptoms and problematic internet use. ACEs significantly affected depressive symptoms (standardized regression weight, 0.36; P < 0.01), and depressive symptoms also affected problematic internet use (standardized regression weight, 0.40; P < 0.01). We found that depressive symptoms had a significant mediating effect on the relationship between problematic internet use and ACEs. The management of depressive symptoms would be important to prevent problematic internet use in children and adolescents with ACEs.